Prefabrike büyük duvar panoları ile yapılan konut yapısı - Hacımustafaoğlu, M. Cihan (Fen Bilimleri Enstitüsü, 1997)
İnsanoğlunun gereksinim duyduğu ihtiyaçların en başında barınacak bir konut gelmektedir. Bu nedenle yapı üretimine duyulan ihtiyaç hiç bir zaman azalmamıştır. Hızlı, kaliteli ve ekonomik yapı üretim isteği, prefabrikasyon teknolojisinin doğmasına ve hızlı bir şekilde gelişmesine neden olmuştur. İnşaat maliyetleri zamana bağlı olarak hızla artış gösterdiğinden, inşaat sektöründe yapı üretim hızı çok önemli bir yer tutmaktadır. Prefabrikasyon teknolojisi, iklim koşullarından bağımsız, kaliteli, hızlı ve modüler yapı üretimine olanak tanıdığından önemini her geçen gün arttırmaktadır. Bu çalışmada prefabrike büyük duvar ve döşeme panolarıyla oluşturulan 6 katlı bir konut binasının projesi yapılmıştır. Yapının plandaki boyutu 39,10m * 16,15m olup kat yükseklikleri 2,70m'dir. Yapı 1. derece deprem bölgesinde bulunmaktadır. Yapının her iki yön için deprem hesabı, yeni deprem yönetmeliğinde verilen esaslar göz önünde tutularak, bağlantı kirişlerinin çatlamış olup olmamasına göre yapılmıştır. Duvar panolarının birbirleriyle ve döşeme panolarıyla yatayda ve düşeyde oluşturulan birleşimleri, üzerlerine etkiyen yükleri güvenli bir şekilde aktarabilecek şekilde teşkil edilmiştir. Bu şekilde birbirleriyle birleşimleri sağlanan duvar panoları yatay yüklere göre sürekli bir perde gibi davranacaktır. Her iki yönde oluşturulan bu perdeler yapının ana taşıyıcı sistemini meydana getirmektedir. X doğrultusunda perdelerin birbirleriyle bağlantıları kolon gibi kabul edilebilecek geniş birleşimlerle oluşturulmuştur. Bu nedenle yapının bu yöndeki taşıyıcı sistemi perde-çerçeve sistem olarak kabul edilmiş ve hesabı fiktif bir sisteme dönüştürülerek yapılmıştır. Y doğrultusunda ise taşıyıcı sistem perde-perde sistem gibi kabul edilerek hesaplar yapılmıştır. Yapının döşemeleri prefabrike panolardan oluşturulmuştur. Döşemelerin hesabı, panoların mesnetlerime durumları da göz önüne alınarak, panoların taşınması, yerine konulması ve birleşim betonları döküldükten sonra nihai yükleri ile yüklenmeleri durumları dikkate alınarak yapılmıştır. Bina zemini yumuşak killi, zayıf bir zemin olduğundan ve taşıyıcı sistem her iki yöndeki sık perdelerden oluştuğundan temel sistemi olarak radye temel seçilmiştir. Radye temel statik hesabı, sonlu elemanlar yöntemiyle çözüm yapan SAP90 bilgisayar programıyla yapılmıştır. Bu hesaplarda radye temel, zemin özelliğini temsil eden yaylara oturan kalın plak gibi tanımlanmıştır.

The main objective of the current study is to design a 6 storeyed residence building which was constructed with large prefabricated panels. The construction stands in the 1st seismic zone described in the new Turkish Code [8]. The building is 16.20m high from the foundation level, 39.10m*16.15m planwise and will be used as a residence. The height of the floors are 270 cm. System's floor plans and panalization drawings are given in next section. Prefabricated wall panels : In this project the main load carrying system consists of prefabricated large load- bearing panels. The effective thickness of the carrying panels are 16 cm. The construction has three different types of large panels. These panels : a) External load-bearing wall panels b) Internal load-bearing wall panels c) Facade wall panels which is not load-bearing wall panels The facade wall panels and load-bearing wall panels subjected to large shear forces have castellations of different sizes on horizontal and vertical edges. The load-bearing walls subjected to comparatively smaller shear forces may not contain keys on top and bottom edges, but reinforcing loops. Their vertical edges only will have castellations. The wall panels must have at least one erection bolts on their rezervations on the bottom edges. Slabs : The floor slabs are composed of precast panels. The thickness of the slabs are 13 cm. In hazarolous zones due to seismicity, slabs are supported mainly on four edges and occasionally on three or two edges. XV During erection they rest freely on the supports, depending upon the type of connection. It is possible to place reinforcement for negative moment on certain edges together with hooks during fabrication and as the hooks are spliced by welding or by loop after erections, these edges can be considered as continuous edges. With respect to the above discussion, analysis of slabs for vertical loads are carried out in two stages, first for loads during erection resting freely on supports, and second for final loads taking account of the continuity of certain supports. It is appropriate to assume continuity in two adjacent slabs only. Foundation : The construction site is mainly composed of soft glay. The main load-bearing system of our construction is composed of lots of large panels and site is very poor, due to its mechanical properties, therefore a continuous plate foundation system in two directions planwise is selected. The dimensions of the continuous plate foundation is 40.00m* 17.00 m planwise. This foundation system is analysed by SAP90 which is a software based on finite elements method. Tie system : There occurs some forces due to differential settlements, temperature differences between the storeyes and different vertical deformations of two neighboring wall panels. Tensile ties resist these additional forces. Typical tie system is shown in Figure 1. horizontal tie system ;-- vertical connection horizontal connection Figure 1. Tie system XVI Load bearing and shear-wall panels contain vertical reinforcement at edges of panels and openings such as doors and windows. These reinforcement elements are properly applied to those of upper and lower panels at joints. The horizontal joints in between the panels may experience strong shear forces as the number of floors and earthquake effects increase therefore, these joints must contain sufficient amount of shear keys or equivalent amount of mechanical attachments and vertical reinforcements to bear tensile forces acting on these points. The splicing of reinforcements may be lapper or welded. One load-bearing panel may lose its bearing capacity accidentally. In that case, the tie system provides the remaining part of the structure act as a simple beam or cantilever. This is one of the most important function of the tie system. Horizontal connections are critical points in large panel constructions. Correctly detailed horizontal connection not only completes the structure, but also provides fast erection of panels, ease in placement of reinforcing bars and concrete in the connection. In vertical load transfer zone of the horizontal connections, no utility pipe or no incorporation should be placed. Vertical connections transfer vertical shear force between the panels. Structural Analysis : The load bearing structure is a space system formed by interconnection of shearwalls in two perpendicular directions x-x and y-y together with lintels above and below openings, and by construction of floor panels exhibiting diaphragm action. The connections of shear walls with walls perpendicular and in their own plane, and with diaphragms are made rigid against shear forced. Consequently, the shear walls connected with perpendicular walls will have flanges as parts of walls joining perpendicular to them. The effective flange width for two-sided flanges is the smallest of the following values. - 16*bw (bw being width of flange) - height of shear wall cross section -4m - 1/5 of height of building In this study, 16*bw is used as effective flange thickness of both sides. XVU Analysis of the structural system is carried out for : a) Earthquake loads in two directions. b) Vertical loads. In the structural design, the linear elastic theory has been used. The building was analyzed according to established earthquake loads in two directions, according to the lintels were in the case of cracked or uncracked separately. In the design of structures for earthquake loads the stifrhess of lintels are taken as 1.0 EJC and 0.40 EJC and two analysis are made. The first design results are used for proportioning of lintels and the second design results for shear walls. Calculating of lateral loads : First of all the total weight of the building is calculated. W; = Gi + n*Qi Wi : The weight of floor. Gi : Dead load Qi : Live load n : 0.30 (The purpose of usage is a residence) If the structure is of regular structure type and the height is less than 25m the seismic effects in the structure can be obtained through a statical solution under the statical equivalent forces. According to this method every structure shall be designed and constructed to resist minimum total lateral seismic force assumed to act nonconcurrently in the direction of each of the main axes of the structure in accordance with the following formula : Vt = W*A(Ti)/Ra A(Tı) = A0'iT!'S(Tı) Ao : Is a factor which accounts for the seismic intensity of site and the seismic hazard exposure. I S Ra Fi The coefficient of structure importance. Is structural spectrum factor. The reduction factor of earthquake load. Forces influencing to each floor. W;*h; F = V *? 1 l ZW*h; XV1U As a result of the case that rigidity of the shear walls, columns and lintels are constant or may vary with the same law, all the carrying system of the structure may be idealized as defined in [9] to the following Active system. Where Ip is the total inertia moments that is parallel to the earthquake force direction in one storey and k is the spring rotational rigidity in that storey. *-£? *i-1 W; Rj ^U1-MPU O 'Rl "'rtS S£"Mpi Figure 2. Fictive system k depends on the flexural rigidity of the beams connected the shear walls to each other or to the columns in that storey. In this fictive system the bending moment is Mp; which is the shear wall moment just over the floor level. These moments are considered as unknown Xi the following linear equations of system in a number equal to the number of stories. Sy., * Xn + 5U * X + 5U+1 * Xi+1 + 8i,o = 0 (i=l,2,3,,N) From these equations the unknowns Mpj=Xi are solved and the other internal forces are calculated.
Design of a prefabricated reinforced concrete building system with large panels
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Konut yapımı; Konut üretim modelleri; Prefabrikasyon; House construction; Housing production models; Prefabrication